2001
DOI: 10.3354/dao047001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with white spot syndrome virus infection in a Vietnamese rice-shrimp farming system

Abstract: White spot disease (WSD) is a pandemic disease caused by a virus commonly known as white spot syndrome virus (WSSV). Several risk factors for WSD outbreaks have been suggested. However, there have been very few studies to identify risk factors for WSD outbreaks in culture systems. This paper presents and discusses the risk factors for WSSV infection identified during a longitudinal observational study conducted in a Vietnamese rice-shrimp farming system. A total of 158 variables were measured comprising locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 29 publications
0
41
1
Order By: Relevance
“…However, not all farms applied pond biosecurity systems to prevent entry of WSSV carriers likely to reside in the communal canals, and thus such carriers might represent a source of disease (OIE 2014). WSD outbreaks in farms in Vietnam have been associated with the introduction of WSSV-infected decapods and WSSV-contaminated zooplankton (Corsin et al 2001). The use of communal canals also increases the likelihood of ponds receiving poorquality hypertrophic or eutrophic water with potential to cause stress that could in turn induce disease (Lyle-Fritch et al 2006, Huang et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all farms applied pond biosecurity systems to prevent entry of WSSV carriers likely to reside in the communal canals, and thus such carriers might represent a source of disease (OIE 2014). WSD outbreaks in farms in Vietnam have been associated with the introduction of WSSV-infected decapods and WSSV-contaminated zooplankton (Corsin et al 2001). The use of communal canals also increases the likelihood of ponds receiving poorquality hypertrophic or eutrophic water with potential to cause stress that could in turn induce disease (Lyle-Fritch et al 2006, Huang et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It infects several species of penaeid shrimp cultivated in the Eastern/Western Hemispheres (Lu et al 1997, Corsin et al 2001, in addition to a wide range of other decapods and crustaceans, including crabs (Chen et al 2000, Sahul Hameed et al 2001) and fresh water crayfish (Huang et al 2001, Jiravanichpaisal et al 2001. Several studies have confirmed that many suspected decapod carriers of WSSV can transmit the virus to Penaeus monodon (Wongteerasupaya et al 1996, Chang et al 1998, Wang et al 1998.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of WSSV in Vietnam was first confirmed by PCR analyses on samples collected in 1997 (Corsin et al, 2001), but it is not clear how many times the virus was introduced from abroad. Also, it is unclear where WSSV originated and how it subsequently spread to other regions in Vietnam from the original introduction site(s).…”
Section: Introductionmentioning
confidence: 99%